“Monoclonal-Type” Plastic Antibodies for COVID-19 Treatment: What Is the Idea? - Francesco Puoci (Journal of Functional Biomaterials, 2020)
In late December 2019, an outbreak due to a novel coronavirus, initially called 2019-nCoV, was reported in Wuhan, China [...]